The Concept Of Variations In The Construction Industry - Xavier, Grace (Journal of Malaysian and Comparative Law, 1991)
This article aims to explore briefly the concept of variations in the construction industry. Most construction projects are carried out on the terms of a formal building contract based on standard forms. Which form is used depends on the nature of the contract works and the bodies involved.